2022
DOI: 10.3390/molecules27103196
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Volatile Constituents in Root Tuber and Rhizome of Curcuma longa L. Using Fingerprints and Chemometrics Approaches on Gas Chromatography–Mass Spectrometry

Abstract: The root tuber and rhizome of Curcuma longa L., abbreviated, respectively, as RCL and RHCL, are used as different medicines in China. In this work, volatile oils were extracted from RCL and RHCL. Then, gas chromatography–mass spectrometry (GC–MS) was used for RCL and RHCL volatile oils analysis, and 45 compounds were identified. The dominant constituents both in volatile oils of RCL and RHCL were turmerone, (−)-zingiberene, and β-turmerone, which covered more than 60% of the total area. The chromatographic fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Furthermore, turmeric extract attenuated scopolamineinduced memory impairment, inhibited the activity of AChE, and promoted the activation of CREB and the expression of brainderived neurotrophic factor in experimental mice. Li et al (Li H. et al, 2022) found that curcumin improved sevoflurane-induced neuronal cell injury mainly by inhibiting the inflammation, oxidative stress and neuronal apoptosis of the hippocampus. Yu et al (Su et al, 2022) used the Morris water maze test and Western blotting to investigate the effects of curcumin on memory function and GSK3β protein expression in the hippocampus of AD rats.…”
Section: Effects On the Nervous Systemmentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, turmeric extract attenuated scopolamineinduced memory impairment, inhibited the activity of AChE, and promoted the activation of CREB and the expression of brainderived neurotrophic factor in experimental mice. Li et al (Li H. et al, 2022) found that curcumin improved sevoflurane-induced neuronal cell injury mainly by inhibiting the inflammation, oxidative stress and neuronal apoptosis of the hippocampus. Yu et al (Su et al, 2022) used the Morris water maze test and Western blotting to investigate the effects of curcumin on memory function and GSK3β protein expression in the hippocampus of AD rats.…”
Section: Effects On the Nervous Systemmentioning
confidence: 97%
“…Curcumae Longae Rhizoma curcumin (Liu et al, 2022),demethoxycurcumin (Liu et al, 2022), bisdemethoxycurcumin (Liu et al, 2022), ar-turmerone (Manzan et al, 2003), α-turmerone (Manzan et al, 2003), βturmerone (Manzan et al, 2003), β-caryophyllene (Manzan et al, 2003), eucalyptol (Manzan et al, 2003), α-phellandrene (Manzan et al, 2003), (−)-zingiberene (Tang et al, 2022), βsesquiphellandrene (Tang et al, 2022), α-curcumene (Tang et al, 2022), terpinolene (Tang et al, 2022), (−)-β-Pinene (Tang et al, 2022), α-Terpinene (Tang et al, 2022), D-Limonene (Tang et al, 2022), Eucalyptol (Tang et al, 2022), Terpinolene (Tang et al, 2022), Linalool (Tang et al, 2022), α-Terpineol (Tang et al, 2022), (E)-β-Farnesene (Tang et al, 2022), γ-Curcumene (Tang et al, 2022) curcumin1.0% volatile oil7.0% (ml/g) (Chinese Pharmacopoeia Commission, 2020)…”
Section: Chemical Composition Content Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, it has found applications in the quality control of various natural products, including herbal medicines. Traditional analytical methods such as thin-layer chromatography (TLC) [7,8], gas chromatography (GC) [9,10], high-performance liquid chromatography (HPLC) [11,12], gas chromatography-mass spectrometry (GC-MS) [13,14], and DNA molecular marker techniques [15,16] have also been extensively employed for quality control in traditional Chinese medicine (TCM). For instance, DNA sequencing has been utilized to discern Cordyceps from its counterfeits at the molecular level [17].…”
Section: Introductionmentioning
confidence: 99%